1996
DOI: 10.1128/mcb.16.5.1936
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Liver-Enriched Transcription Factor Hepatocyte Nuclear Factor 1 in Transcriptional Regulation of the Factor VIII Gene

Abstract: Coagulation factor VIII is an essential cofactor required for normal hemostatic function. A deficiency in factor VIII results in the bleeding disorder hemophilia A. Despite the fact that the factor VIII gene was cloned a decade ago, the mechanisms which control its transcription remain unresolved. In our studies, we have characterized 12 protein binding sites within the factor VIII promoter by DNase I protection assays performed with rat liver nuclear extracts. Three of these elements (sites 1 to 3) are situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 55 publications
1
47
0
1
Order By: Relevance
“…The downstream region of the transcription start site may contribute to tissue-specific positive or negative regulatory activity and increase or decrease synergistically the activity of the promoter in the 5'-flanking region of exon 1 [2,4,21,29,35]. Therefore, intron 1 may also contribute to the expression of the bovine PrP gene.…”
Section: Discussionmentioning
confidence: 99%
“…The downstream region of the transcription start site may contribute to tissue-specific positive or negative regulatory activity and increase or decrease synergistically the activity of the promoter in the 5'-flanking region of exon 1 [2,4,21,29,35]. Therefore, intron 1 may also contribute to the expression of the bovine PrP gene.…”
Section: Discussionmentioning
confidence: 99%
“…This is much greater than the homology between noncoding exons of most other mammalian genes (or GATA-6 exon Ib), suggesting that this region may have an evolutionarily conserved regulatory function. Although the promoters of cellular genes are classically assumed to be 5Ј to the transcriptional initiation site, there are several examples of regulatory DNA motifs, which bind transcription factors, within the transcription unit itself (43)(44)(45)(46). Moreover, sequences within noncoding exons have in a number of cases been shown to affect the rate of transcription initiation (47)(48)(49)(50).…”
Section: The 5ј-utr Does Not Affect the Rate Or Site Of Translationalmentioning
confidence: 99%
“…The promoters were EF1-α, CMV, hAAT, and fviii. To better focus the experiments, we used truncated hAAT and fviii promoter sequences that retained the minimal transcription initiation function (Mendel et al, 1991;McGlynn et al, 1996;Kalsheker et al, 2002). We found that all four promoters were capable of directing FVIII expression in hepatocyte cell lines, as well as in Hek-293 and CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, FVIII is also expressed at moderate levels in the spleen, kidney, and lymph nodes (McGlynn et al, 1996). Transcriptional activity of both the minimal fviii promoter and the minimal hAAT promoter probably requires hepatocyte nuclear factor 1 (HNF1α), and it is enhanced by the absence of its homologous isoform HNF1β (Mendel et al, 1991;McGlynn et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation